Fibrinogen β chain and FXIII polymorphisms affect fibrin clot properties in acute pulmonary embolism. (21st November 2021) - Klajmon, Adrianna; Chmiel, Jakub; Ząbczyk, Michał; Pociask, Elżbieta; Wypasek, Ewa; Malinowski, Krzysztof P.; Undas, Anetta; Natorska, Joanna
Abstract: Background: Prothrombotic fibrin clot properties, including increased clot density, are in part genetically determined. We investigated whether fibrinogen alpha‐chain gene ( FGA ) c.991A>G (rs6050), fibrinogen beta chain gene ( FGB ) −455G>A (rs1800790) and factor XIII gene ( F13 ) c.103G>T (rs5985) polymorphisms affect plasma fibrin clot properties in patients with acute pulmonary embolism (PE). Methods: As many as 126 normotensive patients with PE, free of cancer, were genotyped by TaqMan assay. Fibrin clot permeability (Ks ), clot lysis time (CLT) and endogenous thrombin potential (ETP) were assessed on admission. Results: The minor allele frequencies were as follows: FGA rs6050 ( n = 62, 0.31), FGB rs1800790 ( n = 40, 0.17) and F13 rs5985 ( n = 49, 0.23). There were no differences related to any of the polymorphisms with regard to demographic, clinical and laboratory data, except for fibrinogen concentration, which was higher in carriers of F13 rs5985 polymorphism ( p = .024), and PE combined with deep‐vein thrombosis, which was less prevalent in FGB rs1800790 polymorphism carriers ( p = .004). Carriers of FGB rs1800790 A allele and F13 rs5985 T allele had lower Ks, prolonged CLT and higher ETP compared with major homozygotes (all p < .05). After adjustment for fibrinogen, all differences remained significant (all p < .01). There were no associations between the FGA rs6050 polymorphism and Ks, CLT or ETP. Conclusion: Our study showed that FGB rs1800790 and F13 rs5985 polymorphisms contribute to the prothrombotic fibrin clot phenotype and these effects are strong enough to be observed in the acute phase of PE.